Inside Back Cover: An Organotrifluoroborate for Broadly Applicable One‐Step 18F‐Labeling (Angew. Chem. Int. Ed. 44/2014). Issue 44 (22nd September 2014) - Liu, Zhibo; Pourghiasian, Maral; Radtke, Mark Alex; Lau, Joseph; Pan, Jinhe; Dias, Gemma M.; Yapp, Donald; Lin, Kuo‐Shyan; Bénard, Francois; Perrin, David M.
<x xml:space="preserve">Abstract</x> Olfactory receptors are protein‐based sensors that can detect various vaporous chemical compounds. In their Communication on page 11798 ff., K. Sato and S. Takeuchi report an electrophysiological technique to record the response to vapor odorants through the reconstituted insect olfactory receptors in mammalian cell lines. Their approach integrates a micro‐electromechanical system and a functional gene expression system.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>